Analytical Investigation of Graphene Oxide-Ethylene Glycoland Graphene Oxide-Water, Nanofluid Flow with the Influence of Viscous Dissipation Over Fluctuating Disk - Rehman, Ali; Raghunatha, K. R.; İnç, Mustafa; Jan, Rashid (Springer, 2024)
This study examines the impact of viscous dissipation past a fluctuating disk on the three-dimensional unsteady incompressible viscous flow of water-based nanofluids. The problem's mathematical modeling entails the formulation of continuity, momentum, and energy equations-three fundamental nonlinear governing equations. The proper transformations were conducted in order to convert a collection of partial differential equations (PDEs) to nonlinear ordinary differential equations (NODEs). The obtained governing equations are then solved analytically using the homotopy analysis method (HAM). The study looks into the effects of many factors. To illustrate the influence of these characteristics, the study displays temperature filed and velocity filed as graphical representations. It is anticipated that this work will progress the field of condensed nanostructure and nanomaterials, providing new directions for future investigation in applications pertaining to heat transfer enhancement.
Keywords: Nanofluid; Fluctuating disk; HAM; Coupled equations